Kondisi Kualitas Air Sungai Gadjah Wong Berdasarkan Parameter Klorofil-a - Yanto Yanto (Jenderal Soedirman University, 2005)
Measurement of water quality is always experience method advanced time by time. Advancing in method of water quality measurement directing to easier, faster and more valid technique. Beside parameters such as DO, BOD5, KMnO4that is always used to determine water quality, chlorophyll-a could be the one of parameters that is used to measure the healthy of water body. Chlorophyll-a is commonly used to measure trophic status of water body. Chlorophyll-a can be measured in easy, fast and valid technique. Therefore, chlorophyll-a could be used as practical methode in measurement of water quality. This research is ordered to find formulative correlation between chlorophyll-a with DO, BOD5, KMnO4. Knowing formula related among those parameters, we know the value of DO, BOD5, KMnO4 only by measure the value of chlorophyll-a. Based on this research formulative correlation between chlorophyll-a with DO, BOD5, KMnO4 is couldnt be founded. But, from this research can be resumed that Gadjah Wong river trophyc status is mesotrophyc-eutrophyc